Seasonal incidence and antibiotic susceptibility patterns of Pasteurellaceae isolated from American bison (Bison bison). - Dyer, N W (2001)
Ninety pharyngeal tonsils were collected from 2-year-old American bison (Bison bison) bulls and sampled for members of the Pasteurellaceae family. Particular attention was paid to seasonal incidence and antimicrobial resistance in serotypes and biovariants. Multiple strains of Pasteurella haemolytica (39%), P. trehalosi (68%), P. multocida (34%) and Haemophilus somnus (13%) were cultured from 86 out of the 90 (96%) tonsil samples. Pasteurella trehalosi was the most common and evenly distributed of the organisms recovered. Pasteurella haemolytica was found in fewer numbers than P. trehalosi, but showed an increase in number of isolates recovered with each sampling period. Pasteurella multocida, both A and D capsular types, was recovered from all sampling periods. No serotype pattern was observed in any of the animal groups sampled. One hundred twenty-seven of 147 (86%) of the isolates were resistant to at least 1 antibiotic, 95/147 (65%) to at least 2 different antibiotics, and 16/147 (11%) to at least 3 antibiotics. The most common resistance pattern observed was to neomycin and spectinomycin (73/147) (49%).